Identification of novel serum autoantibodies for differential diagnosis of autoimmune pancreatitis and pancreatic ductal adenocarcinoma - Felix, Klaus M.; Hauck, Oliver Kai; Schnölzer, Martina; Kempf, Tore; Warnken, Uwe; Schneider, Kathrin; Bergmann, Frank; Fritz, Stefan; Werner, Jens (Pancreas, 2016)
ObjectivesThe lack of specific biochemical markers is a major drawback for the diagnosis of autoimmune pancreatitis (AIP). The aims were to characterize the autoantibody profiles in AIP and pancreatic ductal adenocarcinoma (PDAC) and to identify circulating autoantibodies that could be diagnostic ma
Gesehen am 29.05.2020